The Role of Topical Fluoride in Reducing Caries Risk in Children with Weak Tooth Structure - Sara Hasan Mahmoud Ejbara (Journal of Scientific and Human Dimensions, 2026)
Background: Dental caries remains one of the most prevalent chronic diseases in children worldwide, particularly among those with compromised enamel structure. Objective: This review evaluates the effectiveness of topical fluoride in reducing dental caries in children aged 6–12 years with weak tooth structure, including enamel hypomineralization and developmental defects. Methods: A descriptive literature review was conducted using peer-reviewed articles, WHO and CDC reports, and dental journals. Results: Topical fluoride enhances enamel remineralization by forming fluorapatite, inhibits demineralization, reduces cariogenic bacterial activity, and controls plaque accumulation. Clinical studies report caries reduction of 30–60% with regular fluoride use. Fluoride varnish demonstrates the highest efficacy for high-risk children. Conclusion: Topical fluoride is a safe, cost-effective primary preventive intervention for children with weak enamel. Integration with behavioral and community programs optimizes outcomes.
Keywords: Topical Fluoride; Dental Caries; Enamel Hypomineralization; Remineralization; Preventive Dentistry; Pediatric Dentistry.